Studi Mendalam tentang Partial Discharge pada Transformator Daya: Tantangan dan Analisis Artikel Terpilih: In-depth Study of Partial Discharge in Power Transformers: Challenges and Analysis Selected Articles - M.Chaisar Al Furqon, Furqon (Institut Riset dan Publikasi Indonesia, 2024)
Partial discharge (PD) is an electrical phenomenon that occurs in the insulation of a power transformer when high voltage causes the release of small amounts of electrical energy. Although PD itself does not directly cause damage, this phenomenon can gradually damage the insulation, reduce its effectiveness, and eventually lead to transformer failure if not detected and addressed. PD usually indicates a weakness or defect in the insulation system, such as an air gap, contamination, or damage to the insulation material. This article reviews recent research on PD in power transformers published since 2020 and selects some dominant studies for further analysis. The article identifies challenges in PD detection and analysis, such as sensor sensitivity, signal interference, and the need for more accurate diagnosis methods.